Electrochemical Behavior of Biologically Important Indole Derivatives - Cigdem Karaaslan; Sibel Suzen (International Journal of Electrochemistry)
Voltammetric techniques are most suitable to investigate the redox properties of a new drug. Use of electrochemistry is an important approach in drug discovery and research as well as quality control, drug stability, and determination of physiological activity. The indole nucleus is an essential element of a number of natural and synthetic products with significant biological activity. Indole derivatives are the well-known electroactive compounds that are readily oxidized at carbon-based electrodes, and thus analytical procedures, such as electrochemical detection and voltammetry, have been developed for the determination of biologically important indoles. This paper explains some of the relevant and recent achievements in the electrochemistry processes and parameters mainly related to biologically important indole derivatives in view of drug discovery and analysis.